A Practical guide to teaching foreign languages in the secondary school (New York, NY : Routledge, 2024)
"How can you effectively motivate young people to engage with foreign language learning? How can young people engage with new ideas and cultural experiences within and outside the classroom? The new and fully revised edition of A Practical Guide to Teaching Foreign Languages in the Secondary School offers straightforward advice and inspiration for training teachers, NQTs and teachers in their early professional development. Offering a wide range of strategies for successful teaching in the languages classroom, this third edition includes separate chapters on the core skills of reading, writing, speaking and listening and new chapters on pronunciation and the science of learning. The chapters provide detailed examples of theory in practice, based on the most up-to-date research and practice, as well as links to relevant sources supporting evidence-informed practice and cover: - Strategies for planning engaging lessons - Integrating formative and summative assessment - Digital tools and services for teaching and learning - Helping pupils develop better listening skills - Effective speaking activities - The role of scaffolds and models in developing writing skills - Teaching grammar - The intercultural dimension of language teaching - The role of multilingualism in foreign language education - Engaging with critical pedagogy A Practical Guide to Teaching Foreign Languages in the Secondary School is an essential compendium of support and ideas for all those embarking upon their first steps in a successful career in teaching foreign languages"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Languages, Modern -- Study and teaching (Secondary).; English language -- Study & teaching -- Foreign students